Principles of development of social entrepreneurship: foreign approaches and Kazakhstan - K. B. Kanapiyanova; R. M. Ruzanov (Экономика: стратегия и практика)
Society’s interest in social entrepreneurship, both as a new direction of scientific research and as a practical activity, is growing significantly. Social entrepreneurship refers to a set of interrelated activities aimed at solving social problems by developing the commercial activities of economic agents. This article examines the criteria for the development of social entrepreneurship in the world, including Europe, the United States, and Asian countries, identifies the drivers of socially oriented activities, and presents possible ways to develop social entrepreneurship in the Kazakh economy. Based on the comparative analysis, the features of state support for social entrepreneurship in the world space are identified and the characteristics of the main driving forces that contribute to the emergence and development of social entrepreneurship are presented. It is shown that the formation and development of social entrepreneurship in various countries of the world is heterogeneous. Its features depend not only on the current institutional environment, but also on the historical conditions in which this type of activity is formed. At the same time, a necessary condition for the creation of socially oriented organizations is the political and legal environment that allows creating such organizations, and for their successful functioning and development, socio-cultural conditions and the presence of institutions that study, train and support social entrepreneurship are important. The theoretical significance of this research is to systematize research on the development of social entrepreneurship in the world space. The practical significance lies in the analysis of the experience of implementing social entrepreneurship in various countries. The results of the study are recommended for use in the development of programs for the development of social entrepreneurship in the Kazakh economy.